Yield, Weed Infestation and Seed Quality of Soybean Glycine max L. Merr. under Different Tillage Systems - Dorota Gawęda; Małgorzata Halınıarz; Irena Kluseka; Rafał Cierpiałaa (Journal of Agricultural Sciences)
Soybean is a very valuable crop plant and the soybean crop area is continually increasing in the world and in Poland. The effectiveness of soybean cultivation depends on soil and climatic conditions as well as on appropriate tillage. An alternative for plough tillage in the cultivation of soybean is to grow this crop using no-tillage, the popularity of which is constantly growing. The aim of this study was to compare the effect of conventional tillage CT and no-tillage NT on yield, weed infestation and qualitative seed composition of soybean grown under the conditions of the Lublin Upland. A field study was carried out over the period 2009-2012 at the Czesławice Experimental Farm 51° 18′ 23″ N, 22° 16′ 2″ E . The experiment was set up on loess-derived grey-brown podzolic soil as a split-block design in four replicates. The experimental factors were the following tillage systems: conventional tillage CT and no-tillage NT . The soybean cultivar Nawiko was grown in the experiment. The present study showed that the soybean seed yield obtained under CT was higher by 24.3% than under NT. The main reason of the seeds yield decrease in the NT was less soybean plant density. The significant higher number and weight of weeds were recorded in NT, relative to CT. The oil content in seed harvested from the NT plots was found to be higher by 0.3%